Human resource management responsibilities in private clubs. Issue 2 (3rd April 2017) - Barrows, Clayton; Rogoff, Jenna; Robinson, Michael
ABSTRACT: Private clubs have long been considered a unique segment of the hospitality industry. Clubs are different than other types of hospitality enterprises in many respects, including their ownership, revenue sources, management, and specifically, in the management of human resources. This article focuses on how human resources are managed in one regional chapter of the national association of club managers (New England). First, a focus group of club managers in New England was conducted. Next, a survey was conducted of club managers belonging to the New England chapter of the Club Managers Association of America. Findings suggest that very few clubs have human resource directors; responsibilities tend to be delegated through the organization; clubs have certain human resource management challenges associated with not having a human resource director; and general managers are actively involved in the management of human resources.